Analysis of the Application of Occupational Safety and Health Signs as an Effort to Reduce Risks in Building Construction Projects - Mega Cattleya Prameswari Annissaa Islami; Rizqi Novita Sari; Sinta Dewi (BIOMEJ, 2023)
The construction area is the area that has the most sources of danger. UPN "Veteran" East Java is currently constructing several buildings, such as the addition of lecture halls or the construction of laboratories. The density of the campus area with thousands of students around the construction project makes the risk of danger high. Several cases of students slipping and tripping in the construction area due to scattered building materials, making the application of safety signs need to be considered. This study aims to determine how necessary safety signs are for work safety on the UPN "Veteran" East Java construction project. Where the population used in this activity is students with a sample size of 30 people. The methods used are statistical methods of the ANOVA test, Ergonomic Checklist, and Questionnaire of understanding of safety signs. The results of data processing concluded that the application of OHS signs is needed, especially signs of danger of falling goods, tripping warnings, slipping warnings, and slippery floor warnings